Advances in Biomedical Functions of Natural Whitening Substances in the Treatment of Skin Pigmentation Diseases - Liu, Fan; Qu, Linkai; Li, Hua; He, Jiaxuan; Wang, Lei; Fang, Yimeng; Yan, Xiaoqing; Yang, Qinsi; Peng, Bo; Wu, Wei; Jin, Libo; Sun, Da (Pharmaceutics, 2022)
Pigmentation diseases can lead to significant color differences between the affected part and the normal part, resulting in severe psychological and emotional distress among patients. The treatment of pigmentation diseases with good patient compliance is mainly in the form of topical drugs. However, conventional hydroquinone therapy contributes to several pathological conditions, such as erythema, dryness, and skin desquamation, and requires a longer treatment time to show significant results. To address these shortcomings, natural whitening substances represented by kojic acid and arbutin have gradually become the candidate ingredients of traditional local preparations due to their excellent biological safety. This review focuses on several natural whitening substances with potential therapeutic effects in pigmentation disease and their mechanisms, and a thorough discussion has been conducted into the solution methods for the challenges involved in the practical application of natural whitening substances.